2019
DOI: 10.1186/s41983-019-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Refractory epilepsy and obstructive sleep apnea: is there an association?

Abstract: Background: A high prevalence of obstructive sleep apnea (OSA) has been reported in medically refractory epilepsy patients, and there is increasing evidence that treatment of OSA in refractory epilepsy patients would reduce seizure frequency. Objective: Studying the frequency of occurrence of OSA in a group of refractory epilepsy patients, compared to a matched group with medically controlled epilepsy. Methods: Sixty patients with epilepsy, 30 patients with controlled epilepsy (group I), and 30 patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There is also increasing evidence that treatment of OSA leads to better seizure control among patients with DRE ( Rashed et al, 2019 ). However, this has not been specifically addressed for TLE.…”
Section: Resultsmentioning
confidence: 99%
“…There is also increasing evidence that treatment of OSA leads to better seizure control among patients with DRE ( Rashed et al, 2019 ). However, this has not been specifically addressed for TLE.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we think that up-state dependent synaptic potentiation in cortical neurons during NREM sleep contributes to underlying cellular mechanisms 41 for this operational mechanism leading to sleep-related epilepsy incidence in animal models and human patients. As the subcortical POA functions as the sleep switch 2 , this operational mechanism can underlie sleep-related epilepsy incidence in refractory epilepsy 14,61,62 . Beyond this, this mechanism suggests the translational implication in epilepsy field.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 60 adult PWE demonstrated that older patients and those with a longer epilepsy duration tend to have a higher AHI. 30 Those authors suggested that age and the duration of epilepsy play a role in the pathogenesis of worsened OSA, because the BMI was not higher in PWE with a higher AHI than in nonapneic patients. DRE patients who participated in this study were taking a mean of 4.4 AEDs (range: 3–7 AEDs) at baseline, and taking multiple AEDs is associated with weight gain, which potentially exacerbates or increases the risk of OSA.…”
Section: Discussionmentioning
confidence: 99%